Preparation method and application of Pd-based alloy catalyst for hydrogen production from formic acid
By amino modification of the support SPP and synthesizing the PdX/NH2-SPP catalyst, the problem of carbon dioxide by-product during formic acid dehydration is solved, and a highly efficient and selective formic acid hydrogen production reaction is achieved, which improves the performance and life of the catalyst.
Patent Information
- Application Number
- CN202411697897.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively avoid the harmful byproduct of formic acid during the dehydration process, which limits its application potential in fuel cell hydrogen supply.
The support SPP was modified by using 3-aminopropyltriethoxysilane to enrich the -NH2 groups, and an ultrafine PdX/NH2-SPP catalyst was synthesized by impregnation co-reduction method to catalyze the selective dehydrogenation reaction of formic acid.
It is achieved efficient catalytic decomposition of formic acid at room temperature to produce hydrogen, with the hydrogen conversion rate reaching 3606 (mol H2·mol-1metal·h-1), and the hydrogen selectivity is 100%, which reduces the catalyst cost and improves the service life and catalytic efficiency of the catalyst.
Smart Images

Figure CN119819372A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method and application of a Pd-based alloy catalyst for producing hydrogen from formic acid, and belongs to the field of hydrogen storage materials and hydrogen production. Background Art
[0002] Hydrogen extracted from renewable resources is generally considered as a promising clean energy carrier, and liquid organic hydrogen carriers have attracted considerable attention in the past few decades as potential candidates for reversible hydrogen storage and release.
[0003] Formic acid (FA) is considered to be an excellent hydrogen storage medium due to its non-toxicity, convenient transportation, high stability, rich properties, and high hydrogen content. FA can release H by selective dehydrogenation under mild conditions. 2 (HCOOH→H 2 +CO 2 ). The only byproduct of this reaction, carbon dioxide, can be recycled to FA through a reversible hydrogenation reaction, in principle achieving a carbon-neutral cycle. However, FA dehydration should be avoided as much as possible because the byproduct CO will poison fuel cell catalysts, thus limiting its maximum application potential in fuel cell hydrogen supply. Therefore, finding active and stable catalysts is of great significance for FA-based hydrogen production systems. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a preparation method and application of a Pd-based alloy catalyst for hydrogen production from formic acid, wherein 3-aminopropyltriethoxysilane (APTES) is used to modify the carrier SPP to make the carrier rich in -NH 2 The PdX / NH with ultrafine nano alloy particles is prepared by adsorption and deposition of palladium and X (X = Au, Ag, Ir, Mn, Zn, Ni, etc.) precursors on the functional groups and liquid phase reduction with sodium borohydride. 2 -SPP catalyst.
[0005] According to the first aspect of the present application, a method for preparing a Pd-based alloy catalyst for hydrogen production from formic acid is provided. The present invention uses 3-aminopropyltriethoxysilane to modify the carrier (SPP) so that the carrier is rich in -NH 2 The PdX / NH with ultrafine Pd alloy nanoparticles was synthesized by using palladium salt and other metal salts as metal precursors through impregnation co-reduction method. 2 -SPP (X = Au, Ag, Ir, Mn, Zn, etc.) catalyst.
[0006] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid comprises the following steps:
[0007] S1, reacting a mixture containing carrier SPP, 3-aminopropyltriethoxysilane and solvent under an inert atmosphere, centrifuging, washing and drying to obtain NH 2 -SPP;
[0008] S2, NH 2 -SPP was immersed in a mixed solution containing Pd precursor salt and metal X precursor salt, stirred in an ice-water bath, and a reducing agent solution was added dropwise. The mixture was stirred for reaction, washed, and centrifuged to obtain PdX / NH 2 -SPP catalyst;
[0009] X=Au, Ag, Ir, Mn, Zn or Ni.
[0010] In this application, the vector SPP is obtained by the prior art (Zhang et al., Science, 2012, 336, 1684-1687).
[0011] Optionally, in step S1, the mass ratio of the carrier SPP to 3-aminopropyltriethoxysilane is 1:3 to 1:10.
[0012] Optionally, in step S1, the solvent is toluene.
[0013] Optionally, in step S1, the reaction temperature is 80-85° C., and the condensation reflux is performed for 16-30 hours.
[0014] Optionally, in step S1, the reaction temperature is 83° C., and the reaction is condensed and refluxed for 24 hours.
[0015] Optionally, in step S2, the Pd precursor salt is selected from at least one of sodium tetrachloropalladate, palladium chloride, and palladium nitrate;
[0016] The metal X precursor salt is selected from soluble salts corresponding to the metal X.
[0017] Optionally, the metal X precursor salt is selected from at least one of tetrachloroauric acid, silver nitrate, iridium trichloride, manganese chloride, zinc nitrate, and nickel nitrate.
[0018] Optionally, in step S2, the molar ratio of Pd to X is 9:1 to 1:1.
[0019] Optionally, in step S2, the reducing agent is sodium borohydride.
[0020] Optionally, the molar ratio of the reducing agent to the total amount of metal is 8 to 12:1.
[0021] Optionally, the molar ratio of the reducing agent to the total amount of metal is 10:1.
[0022] As a specific embodiment, the preparation method of the Pd-based alloy catalyst for producing hydrogen from formic acid comprises the following steps:
[0023] (1) Weigh a certain amount of SPP into a dried flask, quickly add anhydrous toluene and 3-aminopropyltriethoxysilane, and fill with nitrogen protection. Use an oil bath to maintain the reaction temperature at 83°C and stir magnetically. After condensation and reflux for 24 hours, centrifuge and wash with ethanol and place in a 100°C oven under vacuum to dry. The resulting white solid is ground and set aside for use, marked as NH 2 -SPP;
[0024] (2) Weigh 100 mg of NH 2 -SPP was dissolved in 5 mL of water and stirred to mix well. A precursor salt of Pd and a mixed solution of a precursor salt of metal X (X = Au, Ag, Ir, Mn, Zn, Ni, etc.) were added to the resulting solution and stirred at room temperature for 4 h;
[0025] (3) Under stirring in an ice-water bath, a freshly prepared sodium borohydride solution with a concentration of 0.2 mol / L was added dropwise to the suspension obtained in step 2), stirred for 4 h, washed, and centrifuged to obtain PdX / NH 2 -SPP catalyst.
[0026] According to the second aspect of the present application, there is provided a PdX / NH 2 -SPP catalyst.
[0027] The PdX / NH 2 -SPP catalyst, the total metal loading is 2.5wt.% to 15wt.%.
[0028] Optionally, the particle size of the alloy nanoparticles composed of Pd and metal X is 0.1-2 nm.
[0029] According to the third aspect of the present application, there is provided a PdX / NH 2 -Application of SPP catalyst in formic acid dehydrogenation. Reaction temperature is 298~333K, conversion frequency is 3606~9978h -1 .
[0030] The PdX / NH 2 -Application of SPP catalyst in formic acid dehydrogenation.
[0031] Alternatively, the catalyst is placed in a formic acid solution and reacted to produce hydrogen.
[0032] Optionally, the reaction temperature is 298-333K.
[0033] Optionally, an additive, sodium formate, is also added to the formic acid solution.
[0034] Optionally, the molar ratio of sodium formate to formic acid is 0 to 1:1.
[0035] The beneficial effects of this application include:
[0036] The preparation method of the Pd-based alloy catalyst for hydrogen production from formic acid provided in the present application comprises modifying the support (SPP) with 3-aminopropyltriethoxysilane to make the support rich in -NH 2 The PdX / NH3O4 nanoparticles with ultrafine Pd-based alloy nanoparticles were synthesized by using palladium salt and other metal salts as metal precursors through an impregnation co-reduction method. 2 -SPP catalyst. The prepared Pd-based alloy catalyst can catalyze the decomposition of formic acid to produce hydrogen at room temperature (25°C), and its hydrogen conversion rate reaches 3606 (mol H 2 ·mol -1 metal·h -1 ), the hydrogen selectivity is 100%. The catalyst preparation process of the present application does not require the addition of any stabilizer, and uses aminosilanized carriers to anchor metal nanoparticles, which not only reduces the catalyst cost, but also can effectively adjust the electronic structure and properties of the active center, improve the catalyst activity, increase the service life of the catalyst and the catalytic efficiency, and show efficient hydrogen production activity and good hydrogen selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the XRD pattern of the Pd-based alloy catalyst prepared in Example 1.
[0038] Figure 2 These are SEM and TEM images of the Pd-based alloy catalyst prepared in Example 1, (a) is the SEM image, and (b) is the TEM image.
[0039] Figure 3 This is the infrared absorption spectrum of the Pd-based alloy catalyst prepared in Example 1.
[0040] Figure 4 This is a diagram of hydrogen production by decomposition of formic acid catalyzed by different alloy types of Pd-based alloy catalysts.
[0041] Figure 5 This is a diagram of hydrogen production from the decomposition of formic acid catalyzed by different metal loadings on Pd-based alloy catalysts.
[0042] Figure 6 This is a diagram of hydrogen production from formic acid decomposition catalyzed by Pd-based alloy catalysts before and after amino modification.
[0043] Figure 7This is a diagram of the decomposition of formic acid to produce hydrogen over Pd-based alloy catalysts with and without additives.
[0044] Figure 8 This is a diagram of hydrogen production by formic acid decomposition catalyzed by Pd-based alloy catalysts at different temperatures. DETAILED DESCRIPTION
[0045] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0046] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0047] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0048] The analysis method in the examples of this application is as follows:
[0049] XRD analysis was performed on a Rigaku SmartLab diffractometer using Cu Kα radiation at 40 kV and 150 mA. The 1D D / teX Ultra250 detector was equipped with an array of linearly arranged x-ray intensity sensing cells for phase discrimination at 2θ = 5–80°.
[0050] SEM analysis SEM imaging of powder samples was performed using a Hitachi S-4800 SEM with a 5 kV cold field emission gun. Samples were deposited on carbon tape and examined without coating.
[0051] TEM analysis was obtained by a JEOL-3200FS field emission transmission electron microscope with an accelerating voltage of 300 kV and captured by a Gatan OneView CMOS camera.
[0052] The instrument used for infrared absorption spectroscopy analysis was a Bruker in-situ infrared spectrometer 70V, with the detector set to RT-DLaTGS and a scanning speed of 10 KHz.
[0053] In the examples of the present application, the conversion frequency (TOF) is calculated as follows:
[0054] Conversion frequency:
[0055]
[0056] Where P is the atmospheric pressure, V is the volume of the generated gas, R is the universal constant of the gas, T is the reaction temperature, and n metal is the number of moles of metal and T is the selected reaction time.
[0057] The preparation of the carrier SPP is obtained by referring to the method disclosed in patent US13 / 288595.
[0058] NH 2 -SPP preparation
[0059] Weigh 2 g of SPP into a dried flask, quickly add 120 mL of anhydrous toluene and 15 g of 3-aminopropyltriethoxysilane, and fill with nitrogen protection. Use an oil bath to maintain the reaction temperature at 83 ° C and stir magnetically. After condensation and reflux for 24 hours, centrifuge and wash with ethanol and place in a 100 ° C oven under vacuum. The resulting white solid is ground and set aside for use, marked as NH 2 -SPP.
[0060] Example 1
[0061] (1) Weigh 100 mg of NH 2 -SPP, dissolved in 5mL water, stirred to mix well.
[0062] (2) Add 3 mL of a 0.025 M solution of sodium tetrachloropalladate and 1 mL of a 0.025 M solution of tetrachloroauric acid to the solution obtained in step (1), and stir at room temperature for 4 h.
[0063] (3) Under stirring in an ice-water bath, 5 mL of 0.2 M sodium borohydride solution was added dropwise to the solution obtained in step (2), and stirring was continued for 4 h.
[0064] (4) The reaction solution obtained in step (3) was centrifuged, then washed three times with deionized water, and dried to obtain a PdAu alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Au 0.25 / NH 2 -SPP.
[0065] Example 2
[0066] The tetrachloroauric acid in step (2) of Example 1 was replaced with silver nitrate, and the other steps were the same as Example 1 to obtain a PdAg alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Ag 0.25 / NH 2 -SPP.
[0067] Example 3 In step (2) of Example 1, tetrachloroauric acid was replaced with iridium trichloride, and the other steps were the same as in Example 1 to obtain a PdIr alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Ir 0.25 / NH 2 -SPP.
[0068] Example 4 In step (2) of Example 1, tetrachloroauric acid was replaced with manganese chloride, and the other steps were the same as in Example 1 to obtain a PdMn alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Mn 0.25 / NH 2 -SPP.
[0069] Example 5 In step (2) of Example 1, tetrachloroauric acid was replaced with zinc nitrate hexahydrate, and the other steps were the same as in Example 1 to obtain a PdZn alloy catalyst with a metal loading of 10 wt.%, denoted as Pd 0.75 Zn 0.25 / NH 2 -SPP.
[0070] Example 6 In step (2) of Example 1, tetrachloroauric acid was replaced with nickel nitrate, and the other steps were the same as in Example 1 to obtain a PdNi alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Ni 0.25 / NH 2 -SPP.
[0071] Example 7
[0072] The operation was the same as in Example 1, except that the amounts of sodium tetrachloropalladate and tetrachloroauric acid were adjusted to obtain PdAu alloy catalysts with total metal loadings of 2.5 wt.%, 5.0 wt.%, 7.5 wt.%, and 15.0 wt.%, respectively.
[0073] Comparative Example 1
[0074] The NH 2 -SPP was changed to SPP, and the other steps were the same as in Example 1 to obtain a PdAu alloy catalyst with a total metal loading of 10 wt.%, denoted as Pd 0.75 Au 0.25 / SPP.
[0075] Catalyst characterization testing
[0076] The catalysts prepared in the above examples were characterized and tested. 0.75 Au 0.25 / NH 2 -SPP catalyst is a typical example.
[0077] like Figure 1 As shown, the Pd prepared in Example 1 0.75 Au 0.25 / NH 2-SPP catalyst XRD patterns show that the diffraction peaks of the three samples at 7.88°, 8.67°, 14.81°, 23.25°, 24.06°, 26.84° and 29.99° correspond to the (011), (200), (301), (501), (033), (600) and (053) crystal planes of MFI molecular sieve (JCPDS No.44-0696), indicating that the framework of SPP molecular sieve remains intact after amine functionalization and doping with Pd and Au. In addition, PdAu / NH 2 The XRD spectrum of the -SPP catalyst did not show any diffraction peaks of metal Pd (JCPDS No.72-0710), which may be due to the high dispersion and low crystallinity of metal Pd. The diffraction peaks at 38.27°, 44.42°, 64.53° and 77.54° correspond to the (111), (200), (220) and (311) planes of metal Au (JCPDS No.89-3697), respectively.
[0078] like Figure 2 As shown, the Pd prepared in Example 1 0.75 Au 0.25 / NH 2 -SPP catalyst SEM and TEM images, (a) is the SEM image, (b) is the TEM image. From the SEM image, it can be seen that PdAu / NH 2 -SPPs are typical positively interacting nanosheets, indicating that amine functional group modification and metal doping do not change their morphology. In addition, transmission electron microscopy (TEM) images show that PdAu / NH 2 -SPP maintains an ordered channel structure and the metal particles in the catalyst are evenly distributed and clearly visible.
[0079] like Figure 3 As shown, the Pd prepared in Example 1 0.75 Au 0.25 / NH 2 -Infrared absorption spectrum of SPP catalyst. It can be seen that compared with the original SPP, the amine-modified SPP has a peak at 962 cm -1 The intensity of the Si-OH characteristic band centered at 1552 cm -1 and 2937cm -1 New absorption peaks appear at , which are attributed to the bending vibration of NH and the asymmetric stretching vibration of CH, respectively.
[0080] Catalytic formic acid decomposition hydrogen production test
[0081] The catalysts of different alloys prepared in Examples 1-6 were used to catalyze the decomposition of formic acid to produce hydrogen. The catalysts were dispersed in a 50 mL two-necked flask containing 5 mL of water, and 0.5 mL of 5 M formic acid solution and 0.0025 mol of sodium formate (FA:SF=1:1) were added. The reaction was carried out at 298 K using magnetic stirring. The results are shown in FIG. Figure 4 , it can be seen that PdAu / NH 2 -SPP exhibited the highest catalytic performance. This is because the alloying of Pd with Au enhanced the metal particles' resistance to neutral poisoning of CO, reduced the surface energy, and optimized the adsorption of FA.
[0082] The catalysts with different metal loadings prepared in Examples 1 and 7 were used to catalyze the decomposition of formic acid to produce hydrogen. The catalysts were dispersed in a 50 mL two-necked flask containing 5 mL of water, and 0.5 mL of 5 M formic acid solution and 0.0025 mol of sodium formate (FA:SF=1:1) were added. The reaction was carried out at 298 K using magnetic stirring. The results are shown in FIG. Figure 5 , it can be seen that the catalytic performance of the catalyst increases with the increase of metal PdAu loading. However, after reaching the maximum value, the catalytic performance decreases with the continuous increase of the metal amount, which may be due to the excessive amount of metal blocking the pores of zeolite and forming larger particles, thereby reducing the catalytic performance.
[0083] The catalysts prepared in Example 1 and Comparative Example 1 before and after amino modification were used to catalyze formic acid decomposition to produce hydrogen. The catalysts were dispersed in a 50 mL two-necked flask containing 5 mL of water, 0.5 mL of 5 M formic acid solution and 0.0025 mol of sodium formate (FA:SF=1:1) were added, and the reaction was carried out at 298 K using magnetic stirring. The results are as follows: Figure 6 It can be seen that when PdAu is directly loaded on unmodified SPP (PdAu / SPP), only a few tens of milliliters of gas are released during the entire reaction. In contrast, the initial TOF is 3606.8h -1 PdAu / NH 2 -SPP showed higher catalytic performance, releasing 122 mL of gas in only 2.5 min, indicating that the amine functional group modification can better anchor the metal and greatly improve the catalytic activity.
[0084] The Pd prepared in Example 1 was 0.75 Au 0.25 / NH 2-SPP catalyst catalyzes the decomposition of formic acid to produce hydrogen. The catalyst is dispersed in a 50mL two-necked flask containing 5mL of water, and experiments are carried out according to the following five conditions: adding 0.5mL of 5M formic acid solution (FA:SF=1:0), adding 0.5mL of 5M formic acid solution and 0.00125mol of sodium formate (FA:SF=1:0.5), adding 0.5mL of 5M formic acid solution and 0.0025mol of sodium formate (FA:SF=1:1), adding 0.5mL of 5M formic acid solution and 0.005mol of sodium formate (FA:SF=1:2), adding 0.0025mol of sodium formate (FA:SF=0:1) and using magnetic stirring to react at 298K. The results are as follows Figure 7 The calculated conversion frequencies (TOF) are 1057.0h -1 、2591.4h -1 、3606.8h -1 、2076.3h -1 and 0h -1 , it can be seen that with the increase of sodium formate dosage, the TOF value presents a volcanic shape. The presence of sodium formate increases the concentration of formate ions in the solution, which is beneficial to the contact between formic acid and the active center. HCOO - The ions may be adsorbed on the catalyst surface, thereby increasing the electron density on the PdAu alloy surface, improving the electric field strength, and ultimately promoting the catalytic performance.
[0085] The Pd prepared in Example 1 was 0.75 Au 0.25 / NH 2 -SPP catalyst catalyzes formic acid decomposition to produce hydrogen. The catalyst is dispersed in a 50mL two-necked flask containing 5mL of water, and 0.5mL of 5M formic acid solution and 0.0025mol of sodium formate (FA:SF=1:1) are added. With magnetic stirring, the reaction is carried out at 298K, 313K, and 333K, respectively. The results are as follows Figure 8 It can be seen that the catalytic performance is positively correlated with the reaction temperature, and the performance of the catalyst improves significantly with the increase of temperature. TOF reaches 4468.1h at 313K -1 , reaching 9978.8h at 333K -1 .
[0086] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, characterized in that: The following steps are involved: S1, reacting a mixture containing carrier SPP, 3-aminopropyltriethoxysilane and solvent under an inert atmosphere, centrifuging, washing and drying to obtain NH2-SPP; S2, immersing NH2-SPP in a mixed solution containing Pd precursor salt and metal X precursor salt, stirring in an ice water bath, dropping a reducing agent solution, stirring for reaction, washing, and centrifuging to obtain a PdX / NH2-SPP catalyst; X=Au, Ag, Ir, Mn, Zn or Ni.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the carrier SPP to 3-aminopropyltriethoxysilane is 1:3 to 1:
10.
3. The preparation method according to claim 1, characterized in that: In step S1, the reaction temperature is 80-85° C., and the reaction is condensed and refluxed for 16-30 hours.
4. The preparation method according to claim 1, characterized in that: In step S2, the Pd precursor salt is selected from at least one of sodium tetrachloropalladate, palladium chloride, and palladium nitrate; The metal X precursor salt is selected from a soluble salt corresponding to metal X; Preferably, the metal X precursor salt is selected from at least one of tetrachloroauric acid, silver nitrate, iridium trichloride, manganese chloride, zinc nitrate and nickel nitrate.
5. The preparation method according to claim 1, characterized in that: In step S2, the molar ratio of Pd to X is 9:1 to 1:
1.
6. The preparation method according to claim 1, characterized in that: In step S2, the reducing agent is sodium borohydride; Preferably, the molar ratio of the reducing agent to the total amount of metal is 8 to 12:
1.
7. The PdX / NH2-SPP catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The total metal loading is 2.5wt.% to 15wt.%; Preferably, the particle size of the alloy nanoparticles composed of Pd and metal X is 0.1-2.0 nm.
8. Use of the PdX / NH2-SPP catalyst prepared by the preparation method according to any one of claims 1 to 6 in formic acid dehydrogenation.
9. The use according to claim 8, characterized in that: The catalyst is placed in a formic acid solution to react and obtain hydrogen.
10. The use according to claim 9, characterized in that: The reaction temperature is 298-333K; Preferably, an additive sodium formate is also added to the formic acid solution; Preferably, the molar ratio of sodium formate to formic acid is 0 to 1:1.
Citation Information
Patent Citations
One-step synthesis of mesoporous pentasil zeolite with single-unit-cell lamellar structural features
US9180413B2